PENERAPAN PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK POP-UP BOOK BERBASIS KEARIFAN LOKAL RIAU TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Delita Gustriani; Rita Arianti (STKIP ROKANIA, 2019)
Thematic learning involves several subjects to provide meaningful learning experiences for students by paying attention to regional characteristics and promoting cultural values ​​as local wisdom. The role of the media in the thematic learning process is very important. The presence of media can support the learning process, facilitate students in understanding learning materials, and improve the quality of teacher teaching which will have an impact on the quality of student learning outcomes. The purpose of this study was to find out the learning outcomes in the application of the development of Pop-Up Book thematic learning media based on Riau local wisdom in the grade IV of Elementary School. This type of research is classroom action research consisting of one cycle. This research was conducted at SD Negeri 08 Rambah. The data collection technique performed is a formative test in the form of a written test. Data are analyzed qualitatively and quantitatively. The results value of completeness in the first meeting was 76.14% and increased in the second meeting which was 90.47 % with an average completeness of 83.33%. This means that it has achieved complete completeness in the classical 80% with a very good category. It can be concluded that the application of Pop-Up Book thematic learning media based on Riau local wisdom can improve the learning outcomes of grade IV elementary school students.